THE BRAIN'S PERCEPTION OF LANGUAGE AS A MEANS OF COMMUNICATION: THE STUDY OF EXTERNAL INFLUENCES - Zokirova Sohiba Mukhtoraliyevna (Western European Studies, 2024)
This article examines the brain's perception of language as a primary tool for communication, focusing on how external factors such as environmental stimuli, cultural context, and social interaction shape linguistic comprehension and expression. By investigating various studies and experiments on language processing, this paper outlines the role of external influences in language development and the brain's adaptive responses. The findings suggest that external factors significantly affect both the cognitive and neurological aspects of language perception, highlighting the complexity of language acquisition and communication.
Keywords: Language perception; communication; acquisition; factors